Modern Australian macroeconomics : an open economy policy oriented approach - Layton, Allan P. (Nelson, 1994)
This book is divided into five parts: Fundamentals of macroeconomics; A basic theoretical approach; The Australian macroeconomic institutional setting; Implementation aspects of macroeconomic policy; and Case studies.